2018
DOI: 10.1007/s11356-018-2300-z
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CASC15 promotes tongue squamous carcinoma progression through targeting miR-33a-5p

Abstract: Long non-coding RNAs (lncRNAs) have gained a lot of attention because they participate in several human disorders, including tumors. This study determined the role of LncRNA CASC15 (cancer susceptibility candidate 15) in the development of tongue squamous cell carcinoma (TSCC). Here, we identified that CASC15 expression was upregulated in TSCC samples and cell lines. We showed that overexpression of CASC15 promoted cell proliferation, cycle, and migration in TSCC. In addition, we revealed that miR-33a-5p expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Future studies may also focus on the mechanism of the actions of CASC15 in TSCC. It is worth noting that Zuo et al in a recent study investigated the role of CASC15 in TSCC and they found that CASC15 can target miR-33a-5p to regulate the migration of TSCC cells [18], which is consistent with the data of our studies. However this study also showed that CASC15 overexpression resulted in the accelerated proliferation of TSCC cells, which is inconsistent with our study.…”
Section: Discussionsupporting
confidence: 92%
“…Future studies may also focus on the mechanism of the actions of CASC15 in TSCC. It is worth noting that Zuo et al in a recent study investigated the role of CASC15 in TSCC and they found that CASC15 can target miR-33a-5p to regulate the migration of TSCC cells [18], which is consistent with the data of our studies. However this study also showed that CASC15 overexpression resulted in the accelerated proliferation of TSCC cells, which is inconsistent with our study.…”
Section: Discussionsupporting
confidence: 92%
“…For example, in osteosarcoma, overexpression of lncRNA DANCR inhibits the expression of miR-33a-5p; 21 and in tongue squamous carcinoma, lncRNA CASC15 targetedly inhibits miR-33a-5p. 22 However, the interaction between EGOT and miR-33a-5p has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Zuo et al (81) have reported that lncRNA CASC15 downregulates miR-33a-5p by miRNA sponging, thereby upregulating the miR-33a-5p target ZEB1 and enhancing the proliferation, migration and cell cycle of TSCC cells (Fig. 5B).…”
Section: Tongue Squamous Carcinoma (Tscc)mentioning
confidence: 97%